Enhancing sand screen performance with integrated slurry testing and CFD-DEM modelling - Noorhaslin Che Su; Sofyah Anis Izwani Jusof; Aimi Zahraa Zainal; Yeong Yuan Jian; Chan Kai Xian; Afiq Mohd Laziz; Muhmmad Fadhli Muhammad; Javed Akhbar Khan; Abdul Hazim Abdullah; Mohd Azuwan Maoinser (Heliyon)
Understanding the behavior of sand screens is crucial for optimizing sand control strategies and preventing wellbore failure, which can significantly impact reservoir management and production efficiency. This paper presents a comprehensive experimental and numerical modeling study on sand screen performance, aimed at providing insights prior to real-field applications. The study evaluated a 200-μm wire-wrapped screen (WWS) using slurry tests to determine the amount of sand retained, sand produced and retained permeability to assess screen efficiency. The particle size distribution (PSD) of sand samples was crucial for selecting the appropriate screen size, with results showing that highly uniform and well-sorted sand exhibited higher sand retention and lower sand production due to reduced fines content and maximized void spaces, enhancing fluid flow while mitigating sand production. A coupled Computational Fluid Dynamics-Discrete Element Method (CFD-DEM) simulation platform was employed to model particle-fluid interactions, using an optimal mesh size of 0.005 m. The simulation results showed a high degree of correlation with experimental data, with 93.1 % similarity in sand retention and 63.22 % in sand production. These findings underscore the potential of CFD-DEM simulations in accurately replicating complex sand control processes and optimizing screen performance for enhanced wellbore stability and production efficiency.